Differential diagnosis (occlusion and unocclusal kind) of complicated and diffuse diabetic macular edema with optical coherence tomography method in patients with diabetes type II - O. V. Zborovskaya; N. I. Preuss (Zaporožskij Medicinskij Žurnal)
Introduction. Diabetic macular edema (DME) is a common manifestation of diabetic retinopathy and an important cause of visual impairment in people with diabetes. DME is the most common cause of decreased vision in patients with diabetes. It can accompany any stage of the disease and occurs on average 10% of patients with diabetes. In this case, due to structural changes in the endothelium of retinal vessels violation of the retinal barrier increased permeability of blood vessels wall and fluid accumulation in the intercellular space retinal optical coherence tomography (OCT) is a method of diagnostic morphological structure of the retina and allows high precision of the DME diagnose, assess the severity and observe the dynamics.